2015
DOI: 10.1093/geront/gnv082
|View full text |Cite
|
Sign up to set email alerts
|

How Does Survey Context Impact Self-reported Fraud Victimization?

Abstract: These findings inform the production of new surveys and guide the development of effective social and health policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Fraud susceptibility may also be higher among older adults, who may find new financial scams harder to especially when facing time pressure and high arousal—though reports of age differences in fraud susceptibility vary (AARP Foundation, ; Acierno et al, ; Beals, Carr, Mottola, Deevy, & Carstensen, ; Consumer Financial Protection Bureau, ; Kircanski et al, ; Ross, Grossmann, & Schryer, ; Titus & Gover, ). Even when older adults have relevant financial experiences, they may sometimes find it cognitively too demanding to implement their experience‐based knowledge correctly (Korniotis & Kumar, ), or change their habits to react to new information (Lambert‐Pandraud & Laurent, ; Lambert‐Pandraud, Laurent, & Lapersonne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fraud susceptibility may also be higher among older adults, who may find new financial scams harder to especially when facing time pressure and high arousal—though reports of age differences in fraud susceptibility vary (AARP Foundation, ; Acierno et al, ; Beals, Carr, Mottola, Deevy, & Carstensen, ; Consumer Financial Protection Bureau, ; Kircanski et al, ; Ross, Grossmann, & Schryer, ; Titus & Gover, ). Even when older adults have relevant financial experiences, they may sometimes find it cognitively too demanding to implement their experience‐based knowledge correctly (Korniotis & Kumar, ), or change their habits to react to new information (Lambert‐Pandraud & Laurent, ; Lambert‐Pandraud, Laurent, & Lapersonne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our HRS module (see Online Appendix A) was administered to 1,268 randomly selected survey participants age 50 and older in the 2016 survey wave. 2 In prior research, analysts framing questions about fraud in a criminal context found that it significantly reduced disclosure among 4 women and older people (Beals et al, 2015). Therefore, unlike the HRS Leave Behind surveys that asked respondents to identify themselves as fraud victims, our module queried about specific types of financial decisions and experiences often equivalent to fraud (see also FINRA, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers also face the difficult challenge of verifying how much money was stolen, and how, exactly, assets were misappropriated. Furthermore, cognitively impaired seniors are typically excluded from surveys and seniors tend to underreport fraud relative to other age groups (Beals, Carr, Mottola, Deevy, & Carstensen, 2015). For example, AARP found that only 37% of victims aged 55 and older acknowledged they were defrauded compared with 56% of victims younger than 55 years (Pak & Shadel, 2011).…”
Section: The Present Studymentioning
confidence: 99%